Analys of academic flow, digital literacy and self-regulated learning on academic achievement - Amaliah, Risa Saskiatul; Solihat, Ai Nur; Widyaningrum, Bakti (Educenter : Jurnal Ilmiah Pendidikan, 2023)
The success of learning can basically be seen from the high and low learning outcomes. This research aims to determine the influence of academic flow, digital literacy and self-regulated learning on the academic achievement of Siliwangi Tasikmalaya University students. This research uses an explanatory survey method with a quantitative approach, the population in this research are Siliwangi Tasikmalaya University students class 2018-2021. Sampling in this study used a purposive random sampling technique with a total of 387 students as respondents. The data collection technique uses a questionnaire and the data analysis technique used is multiple linear regression analysis. The research results show that academic flow has a significant effect on student academic achievement, digital literacy has a significant effect on student academic achievement, self-regulated learning has no effect on student academic achievement, academic flow, digital literacy and self-regulated learning simultaneously influence student academic achievement. The coefficient of determination shows that academic flow, digital literacy and self-regulated learning together influence student academic achievement by 8.2 percent and the remaining 91.8 percent is influenced by other factors that are not included careful in this research.